Entrepreneurship Learning Design Based on Tasawuf: Islamic Boarding School Innovation in The Digital Era - Hosaini, Hosaini; Qomar, Mujamil; Kojin, Kojin (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research examines entrepreneurial-based Sufism learning innovations in Islamic boarding schools in the digital era. The object of this research is Islamic boarding schools that have integrated Sufism values ​​with entrepreneurship education in their curriculum. The aim of this research is to explore how the integration of Sufism and entrepreneurship can form students who have a balance between deep spirituality and entrepreneurial skills that are relevant to modern-day challenges. The research method used is a qualitative approach with case studies. Data was collected through in-depth interviews, field observations, and document analysis at Islamic boarding schools that have implemented this approach. This approach is used to understand how Sufism and entrepreneurial learning is implemented and its impact on students. The research results show that the application of entrepreneurial-based Sufism learning can improve students' skills in entrepreneurship while strengthening their understanding of Sufistic values. Digital technology plays an important role in accelerating the learning process and opening up new opportunities in the digital-based business world. In conclusion, the integration of Sufism and entrepreneurship in Islamic boarding schools is able to produce students who are religious, innovative and independent in facing global challenges, proving that Islamic boarding schools can adapt to technological developments without ignoring spiritual values